TANTRA YUKTI METHOD OF THEORIZATION IN AYURVEDA - Singh, Anuradha (Medknow Publications & Media Pvt Ltd, 2003)
Method of theorization (Tantra Yukti-s given in Ayurvedic texts) is analyzed in the backdrop of scientific method. Thirty six methodic devices are singled out from texts for analysis in terms of truth specific, theory specific and discourse specific issues. The paper also points out exact problems in conception of method in Ayurveda and Science.